2013
DOI: 10.1137/120885759
|View full text |Cite
|
Sign up to set email alerts
|

On the cp-Rank and Minimal cp Factorizations of a Completely Positive Matrix

Abstract: We show that the maximal cp-rank of n × n completely positive matrices is attained at a positive-definite matrix on the boundary of the cone of n × n completely positive matrices, thus answering a long-standing question. We also show that the maximal cp-rank of 5 × 5 matrices equals six, which proves the famous Drew-Johnson-Loewy conjecture [Linear Multilinear Algebra, 37 (1994), pp. 303-310] for matrices of this order. In addition we present a simple scheme for generating completely positive matrices of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 25 publications
0
33
0
Order By: Relevance
“…The conjecture was proved for triangle free graphs in [3], for graphs which contain no odd cycle on five or more vertices in [5], for all graphs on five vertices which are not the complete graph in [6], for nonnegative matrices with a positive semidefinite comparison matrix (and any graph) in [7] and for all 5 × 5 CP matrices in [8]. However, the general conjecture is still open.…”
Section: Introductionmentioning
confidence: 99%
“…The conjecture was proved for triangle free graphs in [3], for graphs which contain no odd cycle on five or more vertices in [5], for all graphs on five vertices which are not the complete graph in [6], for nonnegative matrices with a positive semidefinite comparison matrix (and any graph) in [7] and for all 5 × 5 CP matrices in [8]. However, the general conjecture is still open.…”
Section: Introductionmentioning
confidence: 99%
“…(2) and (3) were proven in [20], and (4) follows directly from (3) and Theorem 3.3. The leftmost inequality in (5) follows from (4).…”
Section: Perron-frobenius Perturbationsmentioning
confidence: 77%
“…This proof is an adaptation of one from [20]. In fact, we will prove the more general result that considers M ∈ N n \ {O} with a P-F vector x ∈ R n ++ .…”
Section: Perron-frobenius Perturbationsmentioning
confidence: 91%
See 1 more Smart Citation
“…Shaked-Monderer, Bomze, Jarre & Schachinger [27] showed that the maximal CPrank of nˆn CP-matrices is attained at a positive definite matrix on bdpC n q. Denote R ǹ :" tx P R n | x ě 0u and R ǹ`: " tx P R n | x ą 0u. Dür & Still [15] characterized intpC n q as:…”
Section: Introductionmentioning
confidence: 99%